Galaxies with monstrous black holes in galaxy cluster environments. Issue 1 (11th February 2019) - van Son, Lieke A C; Barber, Christopher; Bahé, Yannick M; Schaye, Joop; Barnes, David J; Crain, Robert A; Kay, Scott T; Theuns, Tom; Dalla Vecchia, Claudio
ABSTRACT: Massive early-type galaxies follow a tight relation between the mass of their central supermassive black hole ( M BH ) and their stellar mass ( M ⋆ ). The origin of observed positive outliers from this relation with extremely high M BH (10^9 M_ ) remains unclear. We present a study of such outliers in the Hydrangea/C-EAGLE cosmological hydrodynamical simulations, designed to enable the study of high-mass galaxy formation and evolution in cluster environments. We find 69 M BH ( M ⋆ ) outliers at z = 0, defined as those with M_BH10^7 M_ and M BH / M ⋆ > 0.01. This paper focuses on a sample of five extreme outliers, that have been selected based on their M BH and M ⋆ values, which are comparable to the most recent estimates of observed positive outliers. This sample of five outliers, classified as 'black hole monster galaxies' (BMGs), was traced back in time to study their origin and evolution. In agreement with the results of previous simulations for lower mass M BH ( M ⋆ ) outliers, we find that these galaxies became outliers due to a combination of their early formation times and tidal stripping. For BMGs with M_BH10^9 M_, major mergers (with a stellar mass ratio of μ > 0.25) at early times (z > 2) precede the rapid growth of their supermassive BHs. Furthermore, the scatter in the relation between M BH and stellar velocity dispersion, σ, correlates positively with the scatter in [Mg/Fe](σ). This indicates that the alpha enhancement of these galaxies, which is closely related to their star formation history, is related to the growth of their central BHs.